2015
DOI: 10.1186/s12937-015-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Dark chocolate and reduced snack consumption in mildly hypertensive adults: an intervention study

Abstract: BackgroundSeveral studies have shown that cocoa and cocoa-containing foods have the potential to lower blood pressure and improve endothelial function. Most of the studies reporting the beneficial effects of dark chocolate on blood pressure have been short (≤ 4 weeks). The aim of the present 8-wks (weeks) study was to assess the effects of regular consumption of dark chocolate during a reduced snack consumption intervention on blood pressure and other cardiovascular risk factors in mildly hypertensive individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
0
18
0
1
Order By: Relevance
“…Various studies reported that the catechins in cocoa could decrease the incidence of cardiovascular diseases with a 70-90 g daily consumption of dark chocolate (Gibble, 2011;Martin, Goya & Ramos, 2013;Kwok, et al, 2015;. However, other studies reported that, with the coexistence of multiple factors such as age, gender, lifestyle including dietary data, cigarette use and insufficient physical activity, chocolate consumption did not have a significant effect on the reduction of the incidence of cardiovascular diseases (Koli, et al, 2015;Kwok, et al, 2016). According to the results of the present study, the female prospective teachers were more conscious about the possibility of a relationship between chocolate consumption and cardiovascular diseases than the male prospective teachers, although they both attended university.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies reported that the catechins in cocoa could decrease the incidence of cardiovascular diseases with a 70-90 g daily consumption of dark chocolate (Gibble, 2011;Martin, Goya & Ramos, 2013;Kwok, et al, 2015;. However, other studies reported that, with the coexistence of multiple factors such as age, gender, lifestyle including dietary data, cigarette use and insufficient physical activity, chocolate consumption did not have a significant effect on the reduction of the incidence of cardiovascular diseases (Koli, et al, 2015;Kwok, et al, 2016). According to the results of the present study, the female prospective teachers were more conscious about the possibility of a relationship between chocolate consumption and cardiovascular diseases than the male prospective teachers, although they both attended university.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that daily consumption of flavanol-rich cocoa products lowered blood pressure (Desch, Schmidt, Kobler, Sonnabend, Eitel, et al, 2010). However, another study suggested that cocoa in chocolate did not lower blood pressure (Koli et al, 2015). The disagreement of the majority of the prospective teachers with the statement chocolate consumption lowers the blood pressure might be due to their inadequate knowledge of the subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, another study found no evidence of an effect of daily intake of dark chocolate (49 g/day) on blood pressure or arterial stiffness in patients with mild hypertension (54). The Flaviola Health Study found that cocoa flavanol intake (450 mg) for 1 month decreased systolic and diastolic blood pressure by 4.4 and 3.9 mmHg, pulse wave velocity by 0.4 m/s and led to improved endothelial function in a healthy, primary prevention population, suggesting potential benefits of cocoa in maintain cardiovascular health (49).…”
Section: Polyphenolsmentioning
confidence: 96%
“…In addition, chocolate is frequently associated with pleasure and stress reduction, as well as other properties discussed throughout this review. 16,17 Cocoa polyphenols represent about 5-6% of its dry weight, and are subdivided in 6 groups: flavanols, flavonols, anthocyanins, flavones, flavanones e isoflavones. Cocoa contains flavanols in monomer (epicatechin and catechin), oligomer, and polymer (proanthocyanidins) forms, as well as anthocyanins, flavonol glycosides, clovamide, dideoxyclovamide, phenylethylamine, N-oleoyl-and N-linoleoylethanolamine, and theobromin.…”
Section: Dark Chocolate As Functional Foodmentioning
confidence: 99%